Hope and trust: Public attitudes toward mass COVID-19 testing programs in Guangzhou, China - Tan, Xuanxuan (Frontiers in Psychology, 2022)
Mass testing is one COVID-19 pandemic response strategy. The effect of population-wide testing programs is influenced by public attitudes toward COVID-19 viral tests. However, the public’s attitudes toward mass testing and related factors in mainland China are not adequately understood. This study focuses on pandemic responses during the first wave of the Delta variant outbreak in southern China and explores how residents responded to population-wide mass COVID-19 testing programs. The research relies on data collected from short videos recording residents’ experiences of being in lockdown, media reports, and semi-structured interviews. Thematic analysis was used to analyze the data, and four themes emerged: public attitudes toward mass testing, the technology of viral tests, policy and governance, and cultural practices. The study finds that residents actively participated in mass testing campaigns as mass viral tests are associated with hope and trust. The Reverse Transcription–Polymerase Chain Reaction (RT-PCR), negative test results, lockdown policies, waiting times, medical staff, and media representations are all actors that assemble and mobilize hope and trust. The research reveals some critical factors influencing people’s attitudes toward mass testing policies in response to COVID-19 and provides practical suggestions for public health professionals in rolling out effective population-wide mass COVID-19 testing.